Postoperative radiochemotherapy for gastric adenocarcinoma - Oblak, Irena (Radiology and oncology (Ljubljana), 2009)
Background. To analyze the efficacy of postoperative radiochemotherapy with 5-florouracil (5-FU) and leucovorin (LV) applied in the patients with gastric carcinoma treated in a single institution. Patients and methods. Between 2001 and 2004, 123 patients with resected gastric adenocarcinoma were treated with postoperative concomitant radiochemotherapy with 5-FU and LV. The adjuvant treatment consisted of five cycles of chemotherapy with 5-FU (425mg/m2 IV) andLV (20 mg/m2 IV) and concomitant radiotherapy with the total dose of 45 Gy.Results. The treatment was completed according to the protocol in 82% of patients. The frequency and severity of early toxic effects induced by radiochemotherapy were manageable. Median follow-up time of 56 survivors was 64.5 months (range: 51.7-96.4 months). The 5-year locoregional control (LRC), diseasefree survival (DFS), disease-specific survival (DSS) and overall survival (OS) were 81%, 48.3%, 50.4%, and 48.4%, respectively. The multivariate analysis showed that the tumor involvement of cardia and low intensity of chemotherapy were independent adverse prognostic factors for DSS and OS. More advanced pT-stage and tumors with diffuse growth type according to Lauren were identified as negative independent prognostic factor for OS. They were also on the threshold of statistical significance for DSS. Conclusions. Postoperative radiochemotherapy for gastric carcinoma has acceptable toxicity, and is effective particularly in regard to LRC. High incidence of distant metastases calls for more effective systemic regimens.
Keywords: Adenocarcinoma; Adenokarcinom; Drug Therapy; Gastrectomy; Gastrektomija; Neoplasm Staging; Novotvorba, stadij; novotvorbe; Pathology; preživetje; Preživetje, analiza; radiokemoterapija; Radiotherapy; Stomach Neoplasms; Surgery; Survival Analysis; therapy; tumor; zdravljenje; želodec; Želodec, novotvorbe